Tuberous sclerosis: unusual associations in four cases. - Ilgren, E B (1984)
Tuberous sclerosis is a rare disease with classic primary or secondary changes affecting mainly the cerebrum, skin, kidneys, and heart. Such lesions are generally hamartomatous and thus display malignant features only in rare cases. This paper describes four cases of tuberous sclerosis which were unique in their association with certain unusual congenital, metabolic, and tumorous conditions.